Aplicaciones pedagógicas del envasador semiautomático de líquidos en procesos de transformación Agroindustrial. - Aguilar Mayorga, Milton German (2022)
Into Agroindustry Career dairy processing laboratory, the automatic liquid bottler is essential, because through it, the students make pedagogical learning practices, in order to develop theoretical and practical knowledge, the operation elatboration, maintenance and appication manual teaching of automatic liquid filler, are apphed in the dairy products elaboration, especially liquid products, the purpose this project is for students perform practices, experiments and research with efficient equipment, machinery and instruments for production. For the project execution, they were necessary the background, theoretical framework and research methodology, with the different research types, which helped to solve the problems and fulfill the stated aims. It was made the manual to provide students with true technical information on the proper functioning, maintenance and calibration that can be carried out in the automatic liquid filler, this machinery is essential for the use of packaging in a fast, safe and clean way. It should be noted that its packaging is only suitable for liquid products. For evidencing the machinery use, it was made demonstrative pedagogical practices in the dairy research laboratory, by making yogurt, skim milk and chocolate milk, this practice demonstrated the machinery proper functioning.